Inverter optimization of soft-switching DC-DC converter* - Marek Pastor; Daniel Gordan; Tomáš Basarik; Chiemeka L. Maxwell (Automatika)
The paper describes the influence of the magnetizing inductance of the transformer on zero-voltage switching of the primary transistors in a soft-switching full-bridge dc-dc converter with a controlled rectifier and turn-off snubber. The optimized version of the transformer allows for achieving a full zero-voltage and zero-current turn-on of the primary transistors in a full-bridge soft-switching DC-DC converter. The analysis is verified by measurements on a laboratory model of the converter. The influence of undischarged output capacitances on the efficiency is measured as well. Also, the impact of the GaN transistors on the zero-voltage switching is discussed.